OGP46 Induces Differentiation of Acute Myeloid Leukemia Cells via Different Optimal Signaling Pathways - Zhao, Min; Wang, Jiangyun; Qu, Mei; Zhao, Yao; Wang, Haihua; Ke, Yu; Liu, Ying; Lei, Zi-Ning; Liu, Hong-Min; Hu, Zhenbo; Wei, Liuya; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2021)
Acute myelogenous leukemia (AML) is characterized by blockage of cell differentiation leading to the accumulation of immature cells, which is the most prevalent form of acute leukemia in adults. It is well known that all-trans retinoic acid (ATRA) and arsenic trioxide are the preferred drugs for acute promyelocytic leukemia (APL). However, they can lead to irreversible resistance which may be responsible for clinical failure after complete remission. Moreover, the differentiation therapy of ATRA-based treatment has not been effective against AML cells with t(8;21) translocation. Here we aimed to identify the differentiation effect of OGP46 on AML cell lines (HL-60, NB4 and Kasumi-1), and explore its possible mechanisms. We found that OGP46 has significant inhibitory activity against these cells by triggering cell differentiation with cell-cycle exit at G1/G0 and inhibited the colony formation capacity of the AML cells. It was shown that OGP46 induced the differentiation of NB4 cells transduced via the transcriptional misregulation in cancer signaling pathway viaby PML-RARα depletion, while it activatedwas attributed to the hematopoietic cell lineage and phagosome pathway in Kasumi-1 cells, which are all critical pathways in cell differentiation. These results highlight that OGP46 is an active agent not only in the APL cell line NB4 but also AML-M2 cell lines, expecially including Kasumi-1 with t(8;21) translocation and HL-60. Therefore, OGP46 may be a potential compound for surmounting the differentiation blockage in AML.